Sistem Pendukung Keputusan Untuk menentukan Beasiswa pada SMA Panca Karya Tangerang Dengan Metode Profile Matching - Ibnu Dwi Lesmono (Universitas Bina Sarana Informatika Kota Sukabumi, 2020)
Quality information needed by management to be able to make the right decision, because mistakes in making decisions can result in both moral and material losses, Decision Support System is a computer system that aims to help decision makers make appropriate decisions, which can take into account all aspects of the determined assessment that support decision making to help and facilitate the decision making process. There are many methods that can be used to help make decisions including the profile matching method. This method the author uses to determine precisely the scholarship recipient students, this method is able to select the best alternative from a number of alternatives, in this case that is entitled to receive scholarships based on criteria determined by the scholarship provider, in this case Panca Karya Tangerang High School . The study was conducted by determining aspects and sub-aspects as well as finding the weight value for each sub-aspect, looking for GAP between the profile and the state of the students' data. Then determined the presentation of the two aspects and added together then carried out the ranking process that will determine the optimal alternative, namely the student with the highest score. There are two forms of scholarship recipients used in this study, which are based on family economics and based on student achievement. The results of this study are ranking results from the Profile Matching Method selection based on the criteria that have been determined. Thus this system is expected to help the institution in determining students who will receive scholarships that are able to provide the solutions needed in making the right decision.Keywords: Scholarships, Profile Matching, Decision Support System.